Effects of 5-week pre-season small-sided-game-based training on repeat sprint ability - Rodriguez-Fernández, A.; Sánchez Sánchez, J.; Rodriguez-Marroyo, J. A.; Casamichana, D.; Villa, J. G. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Numerous studies have analyzed during competitive season different conditioning programs to improve soccer players' repeat sprint ability (RSA). However, few studies have focused on analyzing what happens with this ability after small-sided-game- (SSG-) -based training. Thus, the aim of this study was to determine the changes in physical performance after 5 weeks of pre-season training composed of SSGs in amateur soccer players.